Role Of Fine Needle Aspiration Cytology to Analyze Various Causes of Lymphadenopathy - Mandakini M Patel; Sonal L Italiya; Rajnikant D Patel; Reena B Dudhat; Kumarbhargav R Kaptan; Varsha M Baldwa (Medsci Publications, 2013)
Background: Fine needle aspiration cytology (FNAC) is a simple and reliable technique for study of various causes of lymphadenopathy. Aims: To study cytomorphological patterns of FNAC of lymph nodes and its utility in establishing diagnosis of lymphadenopathy. Methods: Total 580 cases of the lymph node FNAC were studied from May 2011 to April 2012 in Cytopathology department of Government Medical College, Surat. Results: Maximum numbers of cases were in the age group of 21-30 years. The most common lesion encountered was tuberculous lymphadenitis (50.52%) followed by metastatic tumours (27.06%), reactive lymph node (14.66%), acute lymphadenitis (5%) and lymphoma (2.76%) respectively. Conclusion: FNAC is safe, rapid and cost-effective method in establishing the diagnosis in large number of cases of lymphadenopathy.